Use of Twitter in Spanish Communication Journals - Victoria Tur-Viñes (Publications, 2018)
This is an exploratory study on the Twitter profiles managed by 30 Spanish Communication journals. The aim is to analyse the profile management, to identify the features of the most interactive content, and to propose effective practices motivating strategic management. The management variables considered were the following: the launch date of the journal and launch of the Twitter profile; published content and frequency of publication; number of publications in 2016; number of Twitter followers. The identification of the features of the most interactive tweets was performed in a 150-unit sample, taking into consideration the following factors: the number of retweets, likes, type of content (motivation), components forming the content, the date and time of publication, and origin of the publication (internal or unrelated). The results reveal notable practices and certain deficiencies in the strategic management of social profiles. Twitter represents an innovative opportunity in scientific dissemination, and it establishes an inalienable strategy for creating and maintaining the brand-journal while retaining the need to strengthen followers’ reciprocity. Other potential uses are suggested.